2010
DOI: 10.2298/pif1004311d
|View full text |Cite
|
Sign up to set email alerts
|

Leafhoppers and cixiids in phytoplasma-infected carrot fields: Species composition and potential phytoplasma vectors

Abstract: SUMMARYThe first molecular analysis of samples collected in southern Bačka (Serbia) confirmed the presence of aster yellows (16SrI) and stolbur phytoplasmas (16SrXII) in insects belonging to the family Cicadellidae, as well as in carrot plants where the insects were collected. A correct identification of the phytoplasmas and their vectors is essential to arrange effective control strategies to prevent diseases associated with phytoplasmas from spreading to carrots and other vegetable crops. In order to enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 12 publications
1
10
0
1
Order By: Relevance
“…We demonstrated directly that P. alienus adults may practice probing on plants other than true grasses, including dicotyledonous plants. This revealed the mechanism by which P. alienus individuals could acquire dicotyledonous‐specific pathogens, as demonstrated in other studies (Riedle‐Bauer et al., ; Drobnjakovic et al., ; Landi et al., ). In consequence, the probing behaviour of P. alienus on a large range of plants should be taken into consideration when evaluating the potential risk of the species as the vector of plant pathogens.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…We demonstrated directly that P. alienus adults may practice probing on plants other than true grasses, including dicotyledonous plants. This revealed the mechanism by which P. alienus individuals could acquire dicotyledonous‐specific pathogens, as demonstrated in other studies (Riedle‐Bauer et al., ; Drobnjakovic et al., ; Landi et al., ). In consequence, the probing behaviour of P. alienus on a large range of plants should be taken into consideration when evaluating the potential risk of the species as the vector of plant pathogens.…”
Section: Discussionsupporting
confidence: 77%
“…However, some data from field studies suggest that P. alienus may also feed on plants other than true grasses. The species was found in abundance on several crops, e.g., in alfalfa and carrot fields (Koppányi, ; Drobnjakovic et al., ), as well as in common ragweed patches [ Ambrosia artemisiifolia L. (Asteraceae)] (Kiss et al., ). Convincing evidence for the possible feeding of P. alienus on dicotyledonous plants was that phytoplasma strains strictly related to dicotyledons were detected in the body of P. alienus (Riedle‐Bauer et al., ; Drobnjakovic et al., ; Landi et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the leafhopper Z. pullula (Zp) was considered in this study as a non‐vector belonging to a group of typhlocybines, so called stipplers, which feed preferentially on mesophyll (Backus et al ). Moreover, other studies reported that specimens of Zp collected from the field tested negative for the presence of phytoplasmas (Jović et al ; Drobnjakovic et al ), and there were no interaction signal results from previous investigations on the ‘ Ca . P. asteris’ membrane protein Amp and proteins from Zp samples (Galetto et al ).…”
Section: Discussionmentioning
confidence: 85%
“…Çalışmamızda belirlenen Cicadellidae türlerinden A. laevis, P. alienus, M. laevis, E. lineolatus, P. leporinus türlerinin çeltik başta olmak üzere birçok tarımsal üründe (buğday, mısır, sebze, yem bitkileri vb.) çeşitli virüs ve benzeri hastalıklarına vektörlük yaparak önemli oranda ürün kayıplarına yol açtıkları farklı çalışmalarda kayıt edilmiştir (Kalkandelen, 1974;Maramorosch & Harris, 1979;Seifers & Harvey 1989;Drobnjaković et al, 2011). Cixiidae familyasından elde edilen türlerden H. obsoletus başta olmak üzere T. desertorum, P. leporinus'un aynı şekide patates ve sebzelerde önemli bazı virüs hastalıklarını (Stolbur-SV) taşıdığı (Sahtiyancı, 1971;Maramorosch & Harris, 1979;Güçlü & Özbek,1988;Çalı et al, 1989;Darimont & Maixner, 2001;Jović et al, 2011) rapor edilmiştir.…”
Section: Yaprakpiresi Türlerinin Belirlenmesiunclassified